ANALYSIS OF CRIMINAL LIABILITY FOR GAMBLING ON PUBLIC ROADS - Maulida Fitri; Muhamad Zainuri; Rahmat Hidayat (West Science Interdisciplinary Studies, 2023)
This study aims to find out how the accountability for criminal acts of gambling on public roads and how the obstacles to accountability for criminal acts of gambling on public roads. The method used in this research is qualitative. The results of this study indicate that gambling is an act that is prohibited by the state and religion, so in this case it is necessary to consider how to respond to prohibited actions. As well as how to apply to the community, the forms of action that arise and unsettle the community after the regulations and laws in force have been slowly destroyed due to the factor of fear felt by members of the public and can harm themselves, their families and the community. The process of ongoing gambling cases disappeared instantly, making the community peaceful and families harmonious in the jurisdiction of the East Mesuji Police. The ending is so that the family economy is increasingly guaranteed with the family willing to work so that it produces better results than before. And is a result of peace efforts in creating a safe society.